THE THEORY OF FUNCTIONAL SYSTEMS AS A BASIS OF MEDICAL STUDENTS’ WORLD VIEW SYSTEM FORMATION - K. V. Sudakov; V. V. Andrianov (Сеченовский вестник)
The article is devoted for using of the theory of functional system in teaсhing process and principle of the systemoquant organization of the normal physiology course for medical students. The coursе is built and unified using the similar scheme, that includes the rise of the questions, formation of the goal, selection of ways to reach it with learning material — lectures and text books. System approach orients the students on the cognition of the whole organism in its close connections with surroundings. It forms systematic outlook of the students for learning of clinical subjects.